NEWS SOURCING OF THE 2011 SOMALI FAMINE: A COMPARISON BETWEEN PANAPRESS AND REUTERS - Dauda, Sharafa; Omar, Bahiyah (2015)
This article uses online news of the 2011 Somali famine, a humanitarian disaster, to investigate the role of alternative transnational news agencies and Western mainstream news agencies in attributing news to sources. The study concludes that Panapress, an African news agency, originally positioned to challenge Western mainstream media narratives, is doing the opposite by supplementing Reuters’ narrative, hence entrenching homogenization of news flow. The study finds that advocacy/ humanitarian groups were the dominant news sources used by both news agencies, indicating resources are at their disposal and that they have the capacity to pool them to mitigate the consequences of the famine. The results also show the use of news sources by Panapress was limited to advocacy/ humanitarian organizations and foreign dignitaries/ leaders only, and failed to cover victims and other groups affected by the famine.